2018
DOI: 10.1097/opx.0000000000001269
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Apple iPad as a Spot-reading Magnifier

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
(32 reference statements)
1
25
0
2
Order By: Relevance
“…Similarly, a vast majority of respondents (87.4%) agreed at least to some extent that it is important for them to use a mainstream device that is adopted by the general public, alluding to the avoidance of tools which may work to separate users from the norm. Interestingly, prior research has found that an iPad and a portable CCTV are essentially equivalent from a functional perspective (Morrice, Johnson, Marinier, & Wittich, 2017;Wittich, Jarry, Morrice, & Johnson, 2018), suggesting that the decision to replace a traditional assistive device with a mainstream solution may be driven by reasons above and beyond functional factors.…”
Section: Replacement Of Traditional Devicesmentioning
confidence: 99%
“…Similarly, a vast majority of respondents (87.4%) agreed at least to some extent that it is important for them to use a mainstream device that is adopted by the general public, alluding to the avoidance of tools which may work to separate users from the norm. Interestingly, prior research has found that an iPad and a portable CCTV are essentially equivalent from a functional perspective (Morrice, Johnson, Marinier, & Wittich, 2017;Wittich, Jarry, Morrice, & Johnson, 2018), suggesting that the decision to replace a traditional assistive device with a mainstream solution may be driven by reasons above and beyond functional factors.…”
Section: Replacement Of Traditional Devicesmentioning
confidence: 99%
“…A criticism of the LuxIQ is that it has been found to have poor test‐retest reliability in assessing lighting conditions in older adults with visual impairments, 39 and to our knowledge, there have been no studies that have investigated the device’s validity. The Apple iPad is an effective assistive technology device already used by individuals with low vision 43–45 . However, previous studies have only examined the basic functionality of the iPad, and there have been no investigations looking at how the device’s display accommodations affect reading speed/ability in the visually impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Vários dispositivos ópticos foram desenvolvidos para aumentar a independência de indivíduos com baixa visão. Dentre eles podemos citar lupas de mão ou montadas em óculos, television readers, sistemas eletrônicos portáteis de aprimoramento de visão conhecidos como Portable Electronic Vision Enhancement Systems (p-EVES) e dispositivos de reconhecimento ótico de caracteres (Wittich, Jarry, Morrice, & Johnson, 2018;Wolffsohn & Peterson, 2003;Trulaske & Meyer, 1997).…”
Section: Resultsunclassified
“…O próprio iPad (Apple, Inc) foi visto como um possível dispositivo de auxílio, devido às suas configurações (Mednick, Jaidka, Nesdole, & Bona, 2017). Entre esses dispositivos estão o Optelec Compact+, Optelec Compact 4HD, Schweizer eMAG 43 e Eschenbach Mobilux Digital sendo exemplos de p-EVES (portable electronic vision enhancement systems), sistemas eletrônicos de aprimoramento de visão portáteis (Wittich, Jarry, Morrice, & Johnson, 2018;Taylor et al, 2017). Porém, a maioria desses dispositivos ainda apresenta alto custo, com dispositivos que chegam até £545, o que dificulta a sua aquisição pelos pacientes (Bray et al, 2017).…”
Section: Introductionunclassified